2020
DOI: 10.1093/genetics/iyaa002
|View full text |Cite
|
Sign up to set email alerts
|

The fission yeast S-phase cyclin Cig2 can drive mitosis

Abstract: Commitment to mitosis is regulated by cyclin-dependent kinase (CDK) activity. In the fission yeast Schizosaccharomyces pombe, the major B-type cyclin, Cdc13, is necessary and sufficient to drive mitotic entry. Furthermore, Cdc13 is also sufficient to drive S phase, demonstrating that a single cyclin can regulate alternating rounds of replication and mitosis, and providing the foundation of the quantitative model of CDK function. It has been assumed that Cig2, a B-type cyclin expressed only during S phase and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…It has been well established that Cdc13–Cdk1 (the fission yeast M-CDK) can compensate for loss of Cig2–Cdk1 (the fission yeast S-CDK) 9 , but it is not clear whether S-CDK can compensate for M-CDK. Early studies using a temperature-sensitive cdc13 mutant showed that Cig2–Cdk1 could initiate but not complete mitosis 17 , 18 , although a more recent study using the temperature-sensitive cdc13-G282D strain has suggested that Cig2–Cdk1 can completely compensate for Cdc13–Cdk1 loss 22 . However, the authors of this study cautioned that this temperature-sensitive mutant might not have eliminated all M-CDK activity from the cell, a potential problem because they reported that cdc13-G282D cells accumulated dividing septated cells at their restrictive temperature, indicating that mitoses were indeed taking place.…”
Section: S-cdk Cannot Complete Mitosismentioning
confidence: 99%
“…It has been well established that Cdc13–Cdk1 (the fission yeast M-CDK) can compensate for loss of Cig2–Cdk1 (the fission yeast S-CDK) 9 , but it is not clear whether S-CDK can compensate for M-CDK. Early studies using a temperature-sensitive cdc13 mutant showed that Cig2–Cdk1 could initiate but not complete mitosis 17 , 18 , although a more recent study using the temperature-sensitive cdc13-G282D strain has suggested that Cig2–Cdk1 can completely compensate for Cdc13–Cdk1 loss 22 . However, the authors of this study cautioned that this temperature-sensitive mutant might not have eliminated all M-CDK activity from the cell, a potential problem because they reported that cdc13-G282D cells accumulated dividing septated cells at their restrictive temperature, indicating that mitoses were indeed taking place.…”
Section: S-cdk Cannot Complete Mitosismentioning
confidence: 99%
“…Thus, these results suggest that there are only quantitative differences in the ability of different CDKs to the control, S-phase, or mitosis. This principle is conserved in fission yeast, where the S-phase CDK-cyclin complex can trigger mitosis [99,100].…”
Section: Specific Cdk-cyclin Complexes Are Not Essential For Entry In...mentioning
confidence: 99%
“…It has been well established that Cdc13-Cdk1 (M-CDK) can compensate for Cig2-Cdk1 (S-CDK) 7 , but it is not clear if S-CDK can compensate for M-CDK. Early studies using a temperature sensitive cdc13 mutant showed that Cig2-Cdk1 could initiate mitosis could not complete it 17,18 , although a more recent study using the temperature sensitive cdc13-G282D, has suggested that Cig2-Cdk1 can completely compensate for Cdc13-Cdk1 22 . However, the authors of this study cautioned that this temperature sensitive mutant might not have eliminated all the M-CDK activity from the cell, a potential problem because they reported cdc13-G282D cells accumulated dividing septated cells at their restrictive temperature, suggesting that mitoses were taking place.…”
Section: S-cdk Can Initiate Mitosis But Not Complete Itmentioning
confidence: 99%